2020
DOI: 10.3389/fphys.2020.00242
|View full text |Cite
|
Sign up to set email alerts
|

Light and Temperature Synchronizes Locomotor Activity in the Linden Bug, Pyrrhocoris apterus

Abstract: Circadian clocks are synchronized with the external environment by light and temperature. The effect of these cues on behavior is well-characterized in Drosophila, however, little is known about synchronization in non-model insect species. Therefore, we explored entrainment of locomotor activity by light and temperature in the linden bug Pyrrhocoris apterus (Heteroptera), an insect species with a strong seasonal response (reproductive diapause), which is triggered by both photoperiod and thermoperiod. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…RNAi silencing of tim-m supports its role in the clock, which is consistent with its oscillatory role in the rat neuronal cells ( Barnes et al 2003 ). Nevertheless, relatively low P. apterus activity levels and their broad peaks (see Kaniewska et al 2020 ) make it difficult to determine whether alterations of clock gene expression cause phase shifts in behavioral outputs. Thus, the role of TIM-m in circadian photoreception, proposed by the fruit fly experiments ( Benna et al 2010 ) and suggested by the altered activity phase in mammals ( Kurien et al 2019 ), could only be addressed in P. apterus with great difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi silencing of tim-m supports its role in the clock, which is consistent with its oscillatory role in the rat neuronal cells ( Barnes et al 2003 ). Nevertheless, relatively low P. apterus activity levels and their broad peaks (see Kaniewska et al 2020 ) make it difficult to determine whether alterations of clock gene expression cause phase shifts in behavioral outputs. Thus, the role of TIM-m in circadian photoreception, proposed by the fruit fly experiments ( Benna et al 2010 ) and suggested by the altered activity phase in mammals ( Kurien et al 2019 ), could only be addressed in P. apterus with great difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…The linden bug P. apterus is a long-established model for studies concerning diapause and photoperiodism (reviewed in (Socha, 1993;Saunders, 2021) and references therein), and recently also the circadian clock in this species was addressed in more detail (Pivarciova et al, 2016;Kaniewska et al, 2020;Kotwica-Rolinska et al, 2021). Linden bugs are typical diurnal animals showing the peak of the activity around the middle of the day.…”
Section: Introductionmentioning
confidence: 99%
“…No studies have yet investigated thermal entrainment in non-bilaterian animals, and few studies have measured circadian behavior during simultaneous light and temperature cycles in any animal. Since the late 1950's, there have been studies of conflicting light and temperature cycles in insects [4,[18][19][20][21][22][23][24], vertebrates [25][26][27][28], protists [29], and cyanobacteria [30]. There have also been studies of light in conjunction with time-restricted feeding in vertebrates [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Current research of sensory conflict is limited by a dearth of comprehensive behavioral experiments. The small literature of sensory conflict studies has examined conflicting light and temperature cycles in insects ( Miyasako et al, 2007; Currie et al, 2009; Watari and Tanaka, 2010; Yoshii et al, 2010; Nikhil et al, 2014; Harper et al, 2016, 2017; Rivas et al, 2018; Kaniewska et al, 2020 ), vertebrates ( Firth and Kennaway, 1989; Valenciano et al, 1997; Moyer et al, 1997; Firth et al, 1999 ), protists ( Bruce, 1960 ), and cyanobacteria ( Lin et al, 1999 ). There have also been studies of light and time-restricted feeding in vertebrates ( Javier Sánchez-Vázquez et al, 1995; Challet et al, 1998; Reierth and Stokkan, 1998; Lague and Reebs, 2000 ).…”
Section: Introductionmentioning
confidence: 99%